2021
DOI: 10.1093/protein/gzab016
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable D-amino acid decarboxylases derived from Thermotoga maritima diaminopimelate decarboxylase

Abstract: Diaminopimelate decarboxylases (DAPDCs) are highly selective enzymes that catalyze the common final step in different lysine biosynthetic pathways, i.e. the conversion of meso-diaminopimelate (DAP) to L-lysine. We examined the modification of the substrate specificity of the thermostable decarboxylase from Thermotoga maritima with the aim to introduce activity with 2-aminopimelic acid (2-APA) since its decarboxylation leads to 6-aminocaproic acid (6-ACA), a building block for the synthesis of nylon-6. Structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Still, the length of the simulations should be long enough to generate conformational sampling of the ground-state region set at the docking stage, but short enough to maintain a conformation close to the initial structure. Our research group has previously shown that ps-scale MD simulations are long enough to allow meaningful counting of binding poses and that running multiple-independent MD simulations is better for sampling than performing a single long simulation. ,,, Additionally, no large difference was found when comparing the ee % obtained from using the top10% or top20% of Rosetta structures for MD simulations (Table S1). Again, only low-energy conformations should be used to avoid working with unfavorable ground states (unfavorable Rosetta interface energies), but the structures should be diverse enough to prevent single outliers from dominating the averaged frequency of NAC conformations.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Still, the length of the simulations should be long enough to generate conformational sampling of the ground-state region set at the docking stage, but short enough to maintain a conformation close to the initial structure. Our research group has previously shown that ps-scale MD simulations are long enough to allow meaningful counting of binding poses and that running multiple-independent MD simulations is better for sampling than performing a single long simulation. ,,, Additionally, no large difference was found when comparing the ee % obtained from using the top10% or top20% of Rosetta structures for MD simulations (Table S1). Again, only low-energy conformations should be used to avoid working with unfavorable ground states (unfavorable Rosetta interface energies), but the structures should be diverse enough to prevent single outliers from dominating the averaged frequency of NAC conformations.…”
Section: Resultsmentioning
confidence: 98%
“…Our research group has previously shown that ps-scale MD simulations are long enough to allow meaningful counting of binding poses and that running multipleindependent MD simulations is better for sampling than performing a single long simulation. 36,37,46,67 Additionally, no large difference was found when comparing the ee% obtained from using the top10% or top20% of Rosetta structures for MD simulations (Table S1). Again, only low-energy conformations should be used to avoid working with unfavorable ground states (unfavorable Rosetta interface energies), but the structures should be diverse enough to prevent single outliers from dominating the averaged frequency , where the H α is positioned close to the catalytic lysine, because of steric hindrance with the small binding pocket (S: small, L: large binding pockets).…”
Section: Scheme 1 Transamination Reaction Mechanism a Amentioning
confidence: 98%
“…The amino acid sequence of DAP decarboxylase was first reported in Bacillus methanolicus in 1993 ( 15 ). Furthermore, the crystal structures of several DAP decarboxylases have been solved, including nine from terrestrial bacteria and two from the marine thermophilic bacteria Thermotoga maritima and Methanocaldococcus jannaschii ( 16 , 17 ). However, it is unknown whether marine DAP-utilizing bacteria metabolize DAP with DAP decarboxylase.…”
Section: Introductionmentioning
confidence: 99%